2009
DOI: 10.1111/j.1365-2729.2008.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Using a wiki to evaluate individual contribution to a collaborative learning project

Abstract: One critical issue arising in the educational use of collaborative learning concerns the teacher's difficulty in evaluating the contribution and participation of each student in group-work. This article aims to illustrate and discuss a methodology that enables evaluation of the collaborative learning process based on co-writing in a wiki environment. After considering the effectiveness of co-writing as a strategy of collaborative learning, the article will highlight issues regarding methods for evaluating each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
1
15

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(114 citation statements)
references
References 26 publications
(28 reference statements)
5
93
1
15
Order By: Relevance
“…This is in line with the study conducted by Chang (2010) who revealed that pair discussions and group work throughout the term encouraged interaction among students. Besides, collaborative writing on wiki showed that members were very engaged in the learning process (Trentin, 2009). The study also revealed that process writing had major impact on understanding the nature of writing and its instruction (Hyland, 2003).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…This is in line with the study conducted by Chang (2010) who revealed that pair discussions and group work throughout the term encouraged interaction among students. Besides, collaborative writing on wiki showed that members were very engaged in the learning process (Trentin, 2009). The study also revealed that process writing had major impact on understanding the nature of writing and its instruction (Hyland, 2003).…”
Section: Discussionmentioning
confidence: 89%
“…One set of related research studies investigated the application of Web 2.0 technologies in collaborative learning, and how such technologies have enabled instructors provide students with learning environments that can enhance interaction among instructors and peers (Beldarrain, 2006;Trentin, 2009). The employment of Web 2.0 tool in language instruction has enhanced students' interaction (Pop, 2010).…”
Section: Review Of Related Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Como trabajo futuro también podemos destacar que para el próximo curso la asignatura «Administración de Sistemas Operativos» (obligatoria de tercer curso de Ingeniería Técnica en Informática de Sistemas) incorporará desarrollo de documentación en wiki con rúbricas similar a (Trentin, 2009). Actualmente ya cuenta con un wiki, WikiUNIX .…”
Section: Conclusionesunclassified